LAYAR – LAYAR FILOSOFIS: Tentang Puisi, Narasi dan Diri dalam Sinema - Bawono, Haryo Tejo (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2009)
Film can be philosophical in the sense that it leads to a profound reflexion. But philosophy can also be filmic in that the ideas are alive and imaginative. Notwithstanding such general impression, this article seeks to look at the connection between philosophy and film in a different way. On the one hand each of them has its own peculiar characteristics. On the other, if there is a possible connection at all, it should be a dialogical connection. And the connection is to be viewed in terms of their poetic and narrative relation to the self. Both film and philosophy -in different ways- are activities of converting the outer world into human inner world; both are activities of creating concept (poetic) that reconfigure again and again the narrative of the self.